Reform's stunted crop - David Orden (New Zealand Institute of Economic Research (NZIER), 2002)
Congress is on the verge of finalizing a new long-term farm bill to replace legislation passed in 1996. The earlier legislation, when it was enacted, received attention for ist potential to end farm subsidies as they had been known. If Congress had adhered to the 1996 law, both the level and year-to-year variability of previous farm support outlays would have been reduced. Instead, when a three-year run of high crop prices collapsed in 1998, lawmakers began appropriating extra support payments on an annual basis. Momentum to 'beef up' the subsidies authorized in this year's farm bill has been building ever since. The 2002 farm bill will provide both fixed direct payments and producer price guarantees for wheat, feed grains, soybeans, rice, and cotton. It will also authorize an expensive new counter-cyclical subsidy program for a large proportion (but, in principle, fixed quantity) of farm output. The new countercyclical payments will provide a third tier of farm commodity support by reauthorizing subsides similar to those of the past. The long-term support given to farmers by the new bill will have predictable effects. Lawmakers have promised a total of 100 billion in commodity support expenditures over the next decade, which assuredly will create production incentives or be captured in higher land values and rents. Yet, the 2002 farm bill's harm can be limited, depending on how it is written. A House-Senate conference committee is hammering out the final language as this article goes to press.
Keywords: 330; Agrarsubvention; Reform; Neuseeland